2013
DOI: 10.1038/emboj.2013.147
|View full text |Cite
|
Sign up to set email alerts
|

Ral mediates activity-dependent growth of postsynaptic membranes via recruitment of the exocyst

Abstract: Remodelling neuronal connections by synaptic activity requires membrane trafficking. We present evidence for a signalling pathway by which synaptic activity and its consequent Ca2+ influx activate the small GTPase Ral and thereby recruit exocyst proteins to postsynaptic zones. In accord with the ability of the exocyst to direct delivery of post‐Golgi vesicles, constitutively active Ral expressed in Drosophila muscle causes the exocyst to be concentrated in the region surrounding synaptic boutons and consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 105 publications
2
76
0
Order By: Relevance
“…2A-H). To ensure that the localization of the mCh: RalA construct represented that of endogenous RalA populations, we fixed wild-type (WT) embryos and stained with a RalA antibody (Teodoro et al, 2013). Planar and apical-basal images of fixed embryos show that endogenous RalA is present during syncytial stages and localizes in a manner similar to mCh:RalA ( Fig.…”
Section: Rapid Furrow Formation and Regression In The Early Syncytialmentioning
confidence: 99%
See 1 more Smart Citation
“…2A-H). To ensure that the localization of the mCh: RalA construct represented that of endogenous RalA populations, we fixed wild-type (WT) embryos and stained with a RalA antibody (Teodoro et al, 2013). Planar and apical-basal images of fixed embryos show that endogenous RalA is present during syncytial stages and localizes in a manner similar to mCh:RalA ( Fig.…”
Section: Rapid Furrow Formation and Regression In The Early Syncytialmentioning
confidence: 99%
“…Embryos were dechorionated in 50% bleach solution and fixed for 1 h 15 min at the interface of heptane and 3.7% formaldehyde in 0.1 M sodium phosphate buffer ( pH 7.4) before being manually devitellinized and stained with Alexa 546-phalloidin (1:200; Molecular Probes), guinea pig anti-RalA (1:500; Teodoro et al, 2013), Hoechst (1:500; Sigma), mouse anti-Lamin (1:100; DSHB) or mouse anti-Sec5 (1:35; Murthy et al, 2010). Secondary antibodies conjugated with Alexa 488 or Alexa 568 (Molecular Probes) were used at 1:500.…”
Section: Embryo Fixation and Immunostainingmentioning
confidence: 99%
“…Among these, the Ras-like GTPase Ral, of which there are two isoforms, RalA and RalB, has emerged as an important polarity regulator in a variety of contexts, including basolateral membrane trafficking and tight junction formation in epithelial cells (Shipitsin and Feig, 2004;Hazelett et al, 2011), polarized migration of fibroblasts and cancer cells (Rossé et al, 2006;Spiczka and Yeaman, 2008) and tumorigenesis (Camonis and White, 2005;Lim et al, 2005;Oxford et al, 2005;Bodemann and White, 2008;Hazelett and Yeaman, 2012). During brain development, Ral is involved in asymmetric division of neuroblasts (Carmena et al, 2011), neuronal migration in the neocortex (Jossin and Cooper, 2011), neurite branching (Lalli and Hall, 2005) and activity-dependent spine growth (Teodoro et al, 2013). RalA also regulates axon initiation in cortical neurons by promoting an interaction between one of its effectors, the exocyst, and the partitioning-defective (Par) Par3-Par6-aPKC (atypical protein kinase C) complex (Lalli, 2009), an evolutionarily conserved master regulator of polarity (Goldstein and Macara, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that the exocyst complex, in co-ordination with the small-GTPase Ral, also cooperatively promotes dendritic spine density in cultured hippocampal neurons. 75 In fact, neuronal depolarization with KCl stimulation was enough to activate Ral and cause increased spine localization of the exocyst complex, along with an increase in spine numbers. At this stage, it is interesting to note that Ral, the exocyst complex and recycling endosomedependent vesicle trafficking play critical roles in membrane addition at the abscission site during the terminal stages of cytokinesis in mammalian cell lines.…”
Section: The Role Of Small Gtpases and Recycling Endosomes In Neuronamentioning
confidence: 99%